Secondary Metabolites Compounds And Bioactivity Extract Of Telang Flowers (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2026)
Indonesia has many medicinal plants that are good for health. Telang flower (Clitoria ternatea L.) is used by the community as a traditional medicine. The purpose of this study is to ascertain what secondary metabolite compounds, antioxidant activity, and toxicity of telang flower extract. Extraction of telang flower was carried out using the maceration method with n-hexane, ethyl acetate, ethanol, and methanol solvents. Antioxidant activity test used 2,2-diphenyl-1-picrylhydrazyl (DPPH), while toxicity to shrimp larvae (Artemia salina) was tested using the Brine Shrimp Lethality Test (BSLT) method. Based on the results of phytochemical tests, telang flowers are understood to include secondary metabolites, such as alkaloids, flavonoids, steroids, triterpenoids, saponins, and phenolics. The antioxidant activity of ethanol extract of telang flower was classified as very strong compared to methanol, ethyl acetate, and n-hexane extracts, with IC50 values of 49.442 ppm, 50.648 ppm, 54.950 ppm, and 59.935 ppm, respectively. Meanwhile, methanol extract showed higher toxicity to Artemia salina than ethanol, et hyl acetate, and n-hexane extracts, with LC50 values of 76.995 ppm, 97.073 ppm, 266.162 ppm, and 297.934 ppm, respectively. Based on these results, ethanol extract of telang flower has antioxidant activity with a very strong category, while methanol, ethyl acetate, and n-hexane extracts are included in the strong category. On the other hand, the toxicity of methanol extracts and n-hexane extracts was not significant. In contrast, the toxicity of methanol and ethanol extracts to Artemia salina was categorized as strong, while the toxicity of ethyl acetate and n-hexane extracts was classified as weak. Telang flowers have potential as an alternative anticancer drug, but further research is needed.